Food-Anticipatory Behavior in Neonatal Rabbits and Rodents: An Update on the Role of Clock Genes - Caba, Mario; Mendoza, Jorge (Frontiers in Endocrinology, 2018)
In mammals the suprachiasmatic nucleus (SCN), the master circadian clock, is mainly synchronized to the environmental light/dark cycle. SCN oscillations are maintained by a molecular clockwork in which certain genes, Period 1-2, Cry1-2, Bmal1 and Clock, are rhythmically expressed. Disruption of these genes leads to a malfunctioning clockwork and behavioral and physiological rhythms are altered. In addition to synchronization of circadian rhythms by light, when subjects are exposed to food for a few hours daily, behavioral and physiological rhythms are entrained to anticipate mealtime, even in the absence of the SCN. The presence of anticipatory rhythms synchronized by food suggests the existence of an SCN-independent circadian pacemaker that might be dependent on clock genes. Interestingly, rabbit pups, unable to perceive light, suckle milk once a day, which entrains behavioral rhythms to anticipate nursing time. Mutations of clock genes, singly or in combination, affect diverse rhythms in brain activity and physiological processes, but anticipatory behavior and physiology to feeding time remains attenuated or unaffected. It had been suggested that compensatory up-regulation of paralogs or subtypes genes, or even non-transcriptional mechanisms, are able to maintain circadian oscillations entrained to mealtime. In the present mini-review we evaluate the current state of the role played by clock genes in meal anticipation, and provide evidence for rabbit pups as a natural model of food-anticipatory circadian behavior.